Successful shared breeding in an artificial nest-box by Common Swift Apus apus and Common Redstart Phoenicurus phoenicurus - Åkesson, Susanne; Andersson, Arne; Pirio, Maxime (Ornis Svecica, 2015)
During the spring 2015, a pair of Common Redstarts Phoenicurus phoenicurus successfully raised a five-chick brood in an artificial nest-box designed for and occupied by a pair of Common Swifts Apus apus in southern Sweden. The breeding was monitored by a nest-box camera, which recorded close interactions between the two species. The Common Redstarts initiated the breeding first and had young in the nest when the Common Swifts arrived and initiated breeding by laying their eggs in a nearby nest cup. The breeding overlapped by 15 days between the second and the fourth week of June when all five of the nestlings of the Common Redstart fledged. The Common Swifts raised two young which fledged in early August.